Nonprofit Risk Management Contingency Planning : Done in a day strategies - Jackson, Peggy M. (New Jersey : John Wiley, 2005)
Business
2011-10-31
Keywords: Nonprofit Risk Management; Risk Management; Planning; Business Planning; Resource Management